Gaussian process estimation of transition redshift - Jesus, J. F. [UNESP]; Valentim, R.; Escobal, A. A. [UNESP]; Pereira, S. H. [UNESP] (IOP Publishing, 2020)
This paper aims to put constraints on the transition redshift zt, which determines the onset of cosmic acceleration, in cosmological-model independent frameworks. In order to do that, we use the non-parametric Gaussian Process method with H(z) and SNe Ia data. The deceleration parameter reconstruction from H(z) data yields zt=0.59+0.12 -0.11. The reconstruction from SNe Ia data assumes spatial flatness and yields zt=0.683+0.11 -0.082. These results were found with a Gaussian kernel and we show that they are consistent with two other kernel choices.